Porous Hydrogels from Nanoemulsion Templates With Different Structures - Zahra Abbasian Chaleshtari; Babak Valipour Goodarzi; Reza Foudazi (Macromolecular Materials and Engineering)
Abstract Porous hydrogels, including physical pores and spaces within the polymer network, exhibit rapid water uptake rates. Synthesizing porous hydrogels through nanoemulsion templating represents a promising avenue for the development of advanced materials with tailored properties. Certain attributes, including but not limited to the ability to tune droplet size, volume fraction, and interdroplet interactions, provide tools to precisely manipulate the structure of nanoemulsions. The main research question is how the colloidal structure of the template changes the characteristics of a polymer network. Therefore, this study investigates the preparation of porous hydrogels using concentrated nanoemulsions as templates where modulating interdroplet interactions results in different pore structures and properties of the polymer network. Nanoemulsions are prepared by dispersing oil droplets in a continuous phase containing poly (ethylene glycol)‐diacrylate (PEGDA) and sodium dodecyl sulfate (SDS). Subsequent photo‐polymerization of PEGDA and removal of the oil phase leaves behind a porous polymer structure. Then, Hydrogels are analyzed to study the relationship between netwrok structures and water uptake capacities. The discussion focuses on how droplet arrangement under the influence of altered concentrations of SDS, provides confinement for changing the crosslink density of the polymer network.